Perspektif Etika dalam Insider Trading - Vera desy Nurmalia; Ratna Listiana Dewanti; Sekar Akrom Faradiza (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2017)
Nowadays, the phenomena of insider trading is more attractive to be explored. Insider trading provides a great advantage for the perpetrators but can harm the others. The Law of Capital Market stated that insider trading is prohibited, however until now it is difficult to be proved. So, the decision to do insider trading is considered to be one of an ethical issue. The aim of this research is to examine the effect of personal benefit and fairness of law against insider trading. Further, this research will examine the ethical aspect by exploring ethical position as mediating variable. This research used a questionnaire to collect data from investors as respondents. The results of this research showed that personal benefit in the form of possibility to obtaining personal gain significantly affect insider trading, while fairness of law had no effect on insider trading. In terms of ethics, an ethical position only able to mediate the relationship between fairness of law and insider trading.